A study on hull form design of a ship - FABRÍCIO FILHO, Luis Carlos (2020)
It goes without saying that energy saving is important now for our world. The study carried out for this master’s thesis has the theme of energy saving a ship. This master’s thesis reports two studies that share the same theme: hull form design of a ship, with a focus on reduction of wave-making resistance by the hull form improvement. In both studies, the importance of the bow form for reduction of wave- making resistance, which my undergraduate thesis has clarified, is a base. In the first study, a bow form design method for a full ship has been developed and its usefulness has been confirmed by model tests. In the second study, a new resistance test method for a fine ship in a CWC (Circulating Water Channel) has been developed to solve the issues present in the traditional resistance test method in a small CWC concerning accuracy in resistance measurement and model ship manufacture. The new method increases the value of the measured total resistance of the most important part of hull by 216 times compared with that of Traditional Resistance Test Method. The models and connection system necessary for the confirmation test of the method in the CWC have been designed. A study on the model manufacture for the test in a CWC was also conducted, in which material, paint and resin were studied from the viewpoints of strength, water tightness and manufacture easiness by actually manufacturing a partial model and by testing it.